Deposition-temperature dependence of structure, ferroelectric property and conduction mechanism of BCZT epitaxial films. Issue 3 (1st February 2021) - Ji, Xiang; Wang, Chuanbin; Harumoto, Takashi; Tian, Yongshang; Zhang, Song; Tu, Rong; Shen, Qiang; Shi, Ji
Abstract: Ba0 · 85 Ca0 · 15 Zr0 · 1 Ti0 · 9 O3 (BCZT) epitaxial films were successfully deposited on (001) Nb-doped SrTiO3 substrate, and the effects of deposition temperatures on the structure, ferroelectric property, and conduction mechanism were studied. The results of XRD and AFM verified the well epitaxial structure with smooth surfaces of the deposited BCZT epitaxial films. BCZT epitaxial films deposited at 650 °C exhibited the best ferroelectric property (2Pr  = 22.91 μC/cm 2, 2EC  = 1702.11 kV/cm) and relatively low leakage current density (7.91 × 10 3 A/cm 2 ). The conduction mechanism of BCZT films corresponds to the space-charge-limited current (SCLC) mechanism and the Fowler-Nordheim (F–N) tunneling mechanism in the low and high electric field range, respectively.